Synthesis, spectral characterization and electrochemical behavior of oxalic acid doped polyanilines. (2022) - Fernando, Jessica; Vedhi, C.
Abstract: Polyanilines doped with different concentrations of oxalic acid have been synthesized by oxidative chemical polymerization using potassium perdisulfate as oxidizing agent. The effect of dopant on the kinetics of polymerization has been studied by UV–VIS spectroscopy. The presence of oxalic acid in the polymer has been studied by FTIR, and morphology by SEM and TEM. The thermal stability of the polymer was investigated by TGA and degree of crystallinity of polyaniline was studied by XRD. The electrochemical behaviour has been studied by cyclic voltammetry (CV) and the phenomenon of charge transport and capacitance was examined by Electrochemical Impedance Spectroscopy (EIS). The morphological study shows the particles to be of nanosize and EIS studies show that these samples have significant double layer capacitance (Cdl ) and can be used as capacitors.